Colored mixture for preventive maintenance of asphalt pavement and preparation method thereof

By paving colored ultra-thin asphalt mixture on the existing colored asphalt pavement, the cross-linking network of modified SBS, modified carbon nanotubes and inorganic pigments and a three-dimensional mesh structure are solved, and pavement restoration, life extension and color effect are achieved.

CN119707360AActive Publication Date: 2025-03-28BEIJING ZHONGTIAN ROAD IND TECH CO LTD
View PDF 8 Cites 0 Cited by

Patent Information

Application Number
CN202510237939.8
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2025-03-03
Publication Date
2025-03-28
Estimated Expiration
2045-03-03

AI Technical Summary

Technical Problem

Due to the poor durability of decolorized asphalt, the existing colored asphalt concrete pavement has short pavement life. Turtle net cracks and pit grooves generally occur within 3-5 years, affecting the road traffic comfort, and the existing maintenance methods cannot effectively solve this problem.

Method used

A colored mixture for preventive maintenance of asphalt pavement was developed. By laying about 2 cm of colored ultra-thin asphalt mixture on the existing pavement, the colored ultra-thin surface modifier prepared by modified styrene-butadiene-styrene block copolymer (SBS), modified carbon nanotubes and inorganic pigments were used to form a cross-linking network and a three-dimensional network structure to improve the mechanical properties of the material.

Benefits of technology

Through this technology, existing colored asphalt pavement can be effectively repaired, extended pavement life, maintained the color effect of the pavement, and improved the anti-aging performance and low-temperature self-repair ability of the pavement.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure SMS_1
    Figure SMS_1
  • Figure SMS_2
    Figure SMS_2
Patent Text Reader

Abstract

The invention discloses a colored mixture for preventive maintenance of an asphalt pavement and a preparation method of the colored mixture, and relates to the technical field of colored asphalt mixtures. A modified styrene-butadiene-styrene block copolymer (SBS), a modified carbon nano tube and an inorganic pigment are used for preparing the colorful ultrathin cover surface modifier, 3-mercaptopropionic acid and double bonds in SBS are subjected to modification based on a mercapto-ene click chemical reaction, carboxyl is grafted to the 3-mercaptopropionic acid, and the color of the colorful ultrathin cover surface modifier is improved. The metal oxide in the inorganic pigment can be subjected to in-situ coordination with the metal oxide in the inorganic pigment to generate salt bonds, so that a cross-linked network is formed, the mechanical property of the material can be effectively improved, a large number of unsaturated double bonds in the material are eliminated, and the material is not prone to aging.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to the technical field of colored asphalt mixtures, in particular to a colored mixture for preventive maintenance of asphalt pavements and a preparation method thereof. Background Art

[0002] With the development of social economy, people have higher and higher requirements for travel. Colored pavement has been widely used in urban chronic systems and landscape roads in recent years due to its good recognition and beautification effect. At present, colored pavement is mainly divided into three types: colored asphalt concrete, colored spraying and colored slurry seal. Color spraying has low mechanical properties and can only be used for landscape trails in parks; colored slurry seal has excellent mechanical properties, but the cost is high, and it is only used for road turns, downhill or sections with prompts. Therefore, the mainstream colored pavement is still colored asphalt concrete. Colored asphalt concrete is a pavement made by mixing and paving crushed stone, decolorized asphalt and color powder. From the overall application effect in recent years, the durability of decolorized asphalt is poor, and the life of colored pavement is short. Generally, serious turtle cracks and potholes appear in 3-5 years, affecting the comfort of road traffic. There is an urgent need to maintain these colored pavements, but the road management department is a bit helpless. If the existing colored pavement is milled off, only colored asphalt pavement can be paved. After 3-5 years, the same problem will still be faced, and the investment is huge. If ordinary asphalt concrete pavement is used, the existing urban slow-moving system will return to its previous state, and the beautification and improvement effects of urban roads in recent years will be lost. In response to this situation, this patent develops a color ultra-thin overlay technology and its additives that can preventively maintain the existing color asphalt pavement. It only needs to lay about 2cm of color ultra-thin asphalt mixture on the existing pavement to repair the existing pavement while ensuring the color effect of the pavement. Summary of the invention

[0003] The purpose of the present invention is to provide a colored mixture for preventive maintenance of asphalt pavement and a preparation method thereof, so as to solve the problems existing in the prior art.

[0004] In order to solve the above technical problems, the present invention provides the following technical solutions: A color mixture for preventive maintenance of asphalt pavement, wherein the weight proportions of the components of the color mixture are: 55-70 parts of coarse aggregate, 20-50 parts of fine aggregate, 5-10 parts of limestone powder, 4.5-6 parts of asphalt and 2-6 parts of color ultra-thin coating modifier; The coarse aggregate has a specification of 3-5 mm, and the fine aggregate has a specification of 0-3 mm; the asphalt is 70# or 90# heavy-duty road petroleum asphalt.

[0005] Preferably, the weight proportions of the components in the colored ultra-thin coating modifier are: 90-100 parts of inorganic pigment, 120-150 parts of modified styrene-butadiene-styrene block copolymer, 1-5 parts of modified carbon nanotubes and 0-30 parts of plasticizer.

[0006] Preferably, the modified styrene-butadiene-styrene block copolymer uses 3-mercaptopropionic acid through a mercapto-ene click chemistry reaction, so that 3-mercaptopropionic acid reacts with double bonds in the styrene-butadiene-styrene block copolymer to modify the styrene-butadiene-styrene block copolymer to obtain a modified styrene-butadiene-styrene block copolymer.

[0007] Preferably, the modified carbon nanotubes are prepared by chain extension reaction of diamine-terminated polydimethylsiloxane and 2,6-pyridinedicarbonyl chloride, and then grafting reaction is carried out between the modified diamine-terminated polydimethylsiloxane and chlorinated carbon nanotubes to obtain modified carbon nanotubes.

[0008] A method for preparing a colored mixture for preventive maintenance of asphalt pavement comprises the following preparation steps: S1. Weigh the inorganic pigment, modified styrene-butadiene-styrene block copolymer, modified carbon nanotube and plasticizer according to the above weight proportions, add them into a double-roll mill, mix them for 5-10 minutes at a temperature of 130-140° C., discharge them, cool them and pelletize them to obtain a colored ultra-thin coating modifier; S2. Weigh the coarse aggregate, fine aggregate, limestone powder, asphalt and colored ultra-thin surface modifier according to the above-mentioned weight proportions, stir and heat the coarse aggregate and fine aggregate to 150-170°C, then add the colored ultra-thin surface modifier and stir for 5-15s, then add the asphalt and limestone powder, and continue stirring for 30-60s to obtain a colored mixture.

[0009] Preferably, the modified styrene-butadiene-styrene block copolymer comprises the following preparation steps: adding styrene-butadiene-styrene block copolymer to cyclohexane with a mass of 20 to 22 times that of the styrene-butadiene-styrene block copolymer, stirring evenly, adding azobisisobutyronitrile with a mass of 0.5% to 0.75% of that of the styrene-butadiene-styrene block copolymer, adding 3-mercaptopropionic acid with a mass of 0.7 to 0.9 times that of the styrene-butadiene-styrene block copolymer dropwise at a temperature of 0 to 5°C and under nitrogen protection, reacting for 10 to 15 minutes after the dropwise addition, heating to 55 to 65°C and reacting for 12 to 14 hours, adding anhydrous ethanol with a mass of 2 to 3 times that of the cyclohexane after the reaction is complete, stirring, and filtering, washing the filtered product with anhydrous ethanol and deionized water for 3 to 5 times, respectively, and drying to obtain the modified styrene-butadiene-styrene block copolymer.

[0010] Preferably, the modified carbon nanotubes include the following steps: adding chlorinated carbon nanotubes to N, N-dimethylformamide with a mass of 15 to 20 times that of the chlorinated carbon nanotubes, ultrasonically dispersing for 15 to 20 minutes, and uniformly dropping a modified diamino-terminated polydimethylsiloxane solution with a mass of 5 to 7 times that of the chlorinated carbon nanotubes at a rate of 2 to 3 mL / min at a temperature of 0 to 5°C. After the dropwise addition is completed, stirring for 24 to 28 hours at a temperature of 25 to 35°C, standing and filtering after the stirring is completed, and drying and grinding the filtered product to obtain the modified carbon nanotubes.

[0011] Preferably, the modified diamine-terminated polydimethylsiloxane solution comprises the following preparation steps: adding the modified diamine-terminated polydimethylsiloxane to N,N-dimethylformamide with a mass 12 to 14 times that of the modified diamine-terminated polydimethylsiloxane, stirring evenly, preparing a modified diamine-terminated polydimethylsiloxane solution for standby use.

[0012] Preferably, the modified diamino-terminated polydimethylsiloxane comprises the following preparation steps: under nitrogen protection, adding diamino-terminated polydimethylsiloxane to dichloromethane with a mass of 10 to 12 times that of the diamino-terminated polydimethylsiloxane, stirring and dissolving, adding triethylamine with a mass of 0.03 to 0.05 times that of the diamino-terminated polydimethylsiloxane at a temperature of 0 to 5°C, stirring and reacting for 2 to 2.5 hours, adding 2,6-pyridinedicarbonyl chloride solution with a mass of 0.3 to 0.5 times that of the diamino-terminated polydimethylsiloxane at a uniform rate of 5 to 8 mL / min after the stirring is completed, stirring and reacting for 2 to 2.5 hours at a temperature of 0 to 5°C, stirring and reacting for 24 to 26 hours at a temperature of 25 to 35°C after the stirring is completed, and removing the dichloromethane solvent by rotary evaporation after the reaction is completed. After the rotary evaporation is completed, vacuum drying is performed to obtain the modified diamino-terminated polydimethylsiloxane.

[0013] Preferably, the 2,6-pyridinedicarbonyl chloride solution comprises the following preparation process: adding 2,6-pyridinedicarbonyl gas to dichloromethane with a mass of 10 to 12 times that of 2,6-pyridinedicarbonyl gas, stirring evenly, and preparing a 2,6-pyridinedicarbonyl chloride solution for standby use.

[0014] Compared with the prior art, the beneficial effects achieved by the present invention are: The present application adopts modified styrene-butadiene-styrene block copolymer (SBS), modified carbon nanotubes and inorganic pigments to prepare a colored ultra-thin coating modifier, wherein 3-mercaptopropionic acid is modified by reacting with double bonds in SBS based on mercapto-ene click chemistry reaction, so that carboxyl groups are connected thereto, and in-situ coordination with metal oxides in inorganic pigments can be carried out to produce salt bonds, thereby forming a cross-linked network, which can effectively improve the mechanical properties of the material, and eliminate a large number of unsaturated double bonds therein, making it less prone to aging; Modified carbon nanotubes are also used in the process. Modified diamino-terminated polydimethylsiloxane is prepared by chain extension reaction of diamino-terminated polydimethylsiloxane and 2,6-pyridinedicarbonyl chloride, and then the modified diamino-terminated polydimethylsiloxane is grafted with chlorinated carbon nanotubes. A three-dimensional network structure is formed by SBS and carbon nanotubes, and particles formed by SBS can be evenly dispersed in the asphalt. The addition of SBS can also improve the low-temperature performance of the asphalt. The pyridine introduced therein forms a reversible metal coordination bond with metal ions such as iron contained in the inorganic pigment, and the remaining amino groups in the diamino-terminated polydimethylsiloxane form a hydrogen bond hybrid cross-linking network with the carboxyl groups in the modified SBS, thereby improving the mechanical properties of the final product. DETAILED DESCRIPTION

[0015] The following will be combined with the embodiments of the present invention to clearly and completely describe the technical solutions in the embodiments of the present invention. Obviously, the described embodiments are only part of the embodiments of the present invention, not all of the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without making creative work are within the scope of protection of the present invention.

[0016] Example 1 S1. Add 2,6-pyridinedicarboxylic acid chloride to dichloromethane with a mass of 10 times that of 2,6-pyridinedicarboxylic acid chloride, stir evenly, and prepare a 2,6-pyridinedicarboxylic acid chloride solution for use; under nitrogen protection, add diamine-terminated polydimethylsiloxane to dichloromethane with a mass of 10 times that of diamine-terminated polydimethylsiloxane, stir to dissolve, add triethylamine with a mass of 0.03 times that of diamine-terminated polydimethylsiloxane at a temperature of 0°C, stir to react for 2h, and after stirring, add diamine-terminated polydimethylsiloxane dropwise at a rate of 5mL / min After the addition of 2,6-pyridinedicarbonyl chloride solution with a mass of 0.3 times that of oxane, stirring and reacting for 2 hours at a temperature of 0°C, stirring and reacting for 24 hours at a temperature of 25°C, after the reaction is completed, the dichloromethane solvent is removed by rotary evaporation, and vacuum drying is performed after the rotary evaporation to obtain modified diamine-terminated polydimethylsiloxane; the modified diamine-terminated polydimethylsiloxane is added to N,N-dimethylformamide with a mass of 12 times that of the modified diamine-terminated polydimethylsiloxane, stirring evenly, preparing a modified diamine-terminated polydimethylsiloxane solution for standby use; S2, adding the chlorinated carbon nanotubes to N, N-dimethylformamide with a mass of 15 times that of the chlorinated carbon nanotubes, ultrasonically dispersing for 15 minutes, and at a temperature of 0°C, uniformly adding a modified diamine-terminated polydimethylsiloxane solution with a mass of 5 times that of the chlorinated carbon nanotubes at a rate of 2 mL / min. After the addition is completed, stirring at a temperature of 25°C for 24 hours, and after the stirring is completed, standing and filtering, and drying the filtered product and grinding it to obtain modified carbon nanotubes; S3, adding styrene-butadiene-styrene block copolymer to cyclohexane with a mass of 20 times that of styrene-butadiene-styrene block copolymer, stirring evenly, adding azobisisobutyronitrile with a mass of 0.5% times that of styrene-butadiene-styrene block copolymer, at a temperature of 0°C and under nitrogen protection, adding 3-mercaptopropionic acid with a mass of 0.7 times that of styrene-butadiene-styrene block copolymer dropwise, reacting for 10 minutes after the addition is complete, heating to 55°C and reacting for 12 hours, adding anhydrous ethanol with a mass of 2 times that of cyclohexane after the reaction is complete, stirring and filtering, washing the filtered product with anhydrous ethanol and deionized water for 3 times respectively, and drying to obtain a modified styrene-butadiene-styrene block copolymer; S4, weighing 90 parts of inorganic pigment, 120 parts of modified styrene-butadiene-styrene block copolymer, 1 part of modified carbon nanotube and 0 parts of plasticizer by weight, and adding them into a double-roll mill, mixing for 5 minutes at a temperature of 130° C., discharging the material, cooling and pelletizing, to obtain a colored ultra-thin coating modifier; S5. Weigh 55 parts of coarse aggregate, 20 parts of fine aggregate, 5 parts of limestone powder, 4.5 parts of asphalt and 2 parts of color ultra-thin surface modifier by weight. Stir the coarse aggregate and fine aggregate and heat them to 150°C. Then add the color ultra-thin surface modifier and stir for 5 seconds. Then add the asphalt and limestone powder and continue stirring for 30 seconds to obtain a color mixture.

[0017] Example 2 S1. Add 2,6-pyridinedicarboxylic acid chloride to dichloromethane with a mass of 11 times that of 2,6-pyridinedicarboxylic acid chloride, stir evenly, and prepare a 2,6-pyridinedicarboxylic acid chloride solution for use; under nitrogen protection, add diamino-terminated polydimethylsiloxane to dichloromethane with a mass of 11 times that of diamino-terminated polydimethylsiloxane, stir to dissolve, add triethylamine with a mass of 0.04 times that of diamino-terminated polydimethylsiloxane at a temperature of 2.5°C, stir to react for 2.25h, and after stirring, add diamino-terminated polydimethylsiloxane dropwise at a rate of 6.5mL / min. After the addition of 2,6-pyridinedicarbonyl chloride solution with a mass of 0.4 times that of siloxane is completed, the reaction is stirred at a temperature of 2.5°C for 2.25 hours, and the reaction is stirred at a temperature of 30°C for 25 hours. After the reaction is completed, the dichloromethane solvent is removed by rotary evaporation, and the reaction is vacuum dried after the rotary evaporation to obtain a modified diamine-terminated polydimethylsiloxane; the modified diamine-terminated polydimethylsiloxane is added to N,N-dimethylformamide with a mass of 13 times that of the modified diamine-terminated polydimethylsiloxane, and the mixture is stirred evenly to prepare a modified diamine-terminated polydimethylsiloxane solution for standby use; S2, adding the chlorinated carbon nanotubes to N, N-dimethylformamide with a mass of 17.5 times that of the chlorinated carbon nanotubes, ultrasonically dispersing for 17.5 minutes, and at a temperature of 2.5°C, uniformly adding a modified diamine-terminated polydimethylsiloxane solution with a mass of 6 times that of the chlorinated carbon nanotubes at a rate of 2.5 mL / min. After the addition is completed, stirring at a temperature of 30°C for 26 hours, and after the stirring is completed, standing and filtering, and drying the filtered product and grinding it to obtain modified carbon nanotubes; S3, adding styrene-butadiene-styrene block copolymer to cyclohexane with a mass of 21 times that of styrene-butadiene-styrene block copolymer, stirring evenly, adding azobisisobutyronitrile with a mass of 0.625% times that of styrene-butadiene-styrene block copolymer, adding 3-mercaptopropionic acid with a mass of 0.8 times that of styrene-butadiene-styrene block copolymer dropwise at a temperature of 2.5°C and under nitrogen protection, reacting for 12.5 minutes after the addition is complete, heating to 60°C and reacting for 13 hours, adding anhydrous ethanol with a mass of 2.5 times that of cyclohexane after the reaction is complete, stirring and filtering, washing the filtered product with anhydrous ethanol and deionized water for 4 times respectively, and drying to obtain a modified styrene-butadiene-styrene block copolymer; S4, weighing 95 parts of inorganic pigment, 135 parts of modified styrene-butadiene-styrene block copolymer, 3 parts of modified carbon nanotubes and 15 parts of plasticizer by weight, and adding them into a double-roll mill, mixing for 7.5 minutes at a temperature of 135° C., discharging the material, cooling and pelletizing, to obtain a colored ultra-thin coating modifier; S5. Weigh 62.5 parts of coarse aggregate, 35 parts of fine aggregate, 7.5 parts of limestone powder, 5.25 parts of asphalt and 4 parts of color ultra-thin coating modifier by weight. Stir the coarse aggregate and fine aggregate and heat them to 160°C. Then add the color ultra-thin coating modifier and stir for 10 seconds. Then add asphalt and limestone powder and continue stirring for 45 seconds to obtain a color mixture.

[0018] Example 3 S1. Add 2,6-pyridinedicarboxylic acid chloride to dichloromethane with a mass of 12 times that of 2,6-pyridinedicarboxylic acid chloride, stir evenly, and prepare a 2,6-pyridinedicarboxylic acid chloride solution for standby use; under nitrogen protection, add diamino-terminated polydimethylsiloxane to dichloromethane with a mass of 12 times that of diamino-terminated polydimethylsiloxane, stir to dissolve, add triethylamine with a mass of 0.05 times that of diamino-terminated polydimethylsiloxane at a temperature of 5°C, stir to react for 2.5h, and after stirring, add diamino-terminated polydimethylsiloxane dropwise at a rate of 8mL / min After the addition of 2,6-pyridinedicarbonyl chloride solution with a mass of 0.5 times that of oxane, stirring and reacting for 2.5 hours at a temperature of 5°C, stirring and reacting for 26 hours at a temperature of 35°C, after the reaction is completed, the dichloromethane solvent is removed by rotary evaporation, and vacuum drying is performed after the rotary evaporation to obtain modified diamino-terminated polydimethylsiloxane; the modified diamino-terminated polydimethylsiloxane is added to N,N-dimethylformamide with a mass of 14 times that of the modified diamino-terminated polydimethylsiloxane, stirring evenly, preparing a modified diamino-terminated polydimethylsiloxane solution for standby use; S2, adding the chlorinated carbon nanotubes to N, N-dimethylformamide with a mass 20 times that of the chlorinated carbon nanotubes, ultrasonically dispersing for 20 minutes, and uniformly adding a modified diamine-terminated polydimethylsiloxane solution with a mass 7 times that of the chlorinated carbon nanotubes at a rate of 3 mL / min at a temperature of 5°C. After the addition is completed, stirring is performed at a temperature of 35°C for 28 hours. After the stirring is completed, the mixture is allowed to stand and filtered, and the filtered product is dried and ground to obtain modified carbon nanotubes; S3, adding styrene-butadiene-styrene block copolymer to cyclohexane with a mass of 22 times that of styrene-butadiene-styrene block copolymer, stirring evenly, adding azobisisobutyronitrile with a mass of 0.75% times that of styrene-butadiene-styrene block copolymer, adding 3-mercaptopropionic acid with a mass of 0.9 times that of styrene-butadiene-styrene block copolymer dropwise at a temperature of 5°C and under nitrogen protection, reacting for 15 minutes after the addition is complete, heating to 65°C and reacting for 14 hours, adding anhydrous ethanol with a mass of 3 times that of cyclohexane after the reaction is complete, stirring and filtering, washing the filtered product with anhydrous ethanol and deionized water for 5 times respectively, and drying to obtain a modified styrene-butadiene-styrene block copolymer; S4, weighing 100 parts of inorganic pigment, 150 parts of modified styrene-butadiene-styrene block copolymer, 5 parts of modified carbon nanotubes and 30 parts of plasticizer by weight, adding them into a double-roll mill, mixing for 10 minutes at a temperature of 140° C., discharging the material, cooling and pelletizing, to obtain a colored ultra-thin coating modifier; S5. Weigh 70 parts of coarse aggregate, 50 parts of fine aggregate, 10 parts of limestone powder, 6 parts of asphalt and 6 parts of color ultra-thin coating modifier by weight. Stir the coarse aggregate and fine aggregate and heat them to 170°C. Then add the color ultra-thin coating modifier and stir for 15 seconds. Then add the asphalt and limestone powder and continue stirring for 60 seconds to obtain a color mixture.

[0019] Example 4 The difference from Example 2 is only in step S2: adding the chlorinated carbon nanotubes to N, N-dimethylformamide with a mass of 17.5 times that of the chlorinated carbon nanotubes, ultrasonically dispersing for 17.5 minutes, and uniformly adding a diamine-terminated polydimethylsiloxane solution with a mass of 6 times that of the chlorinated carbon nanotubes at a rate of 2.5 mL / min at a temperature of 2.5°C. After the addition is completed, stirring is performed for 26 hours at a temperature of 30°C. After the stirring is completed, the mixture is allowed to stand and filtered, and the filtered product is dried and then ground to obtain modified carbon nanotubes; adding the diamine-terminated polydimethylsiloxane to N, N-dimethylformamide with a mass of 13 times that of the diamine-terminated polydimethylsiloxane, stirring evenly, and preparing a diamine-terminated polydimethylsiloxane solution for standby use; Example 5 The only difference from Example 2 is step S4: 95 parts of inorganic pigment, 135 parts of styrene-butadiene-styrene block copolymer, 3 parts of modified carbon nanotubes and 15 parts of plasticizer are weighed by weight, and added into a double-roll mill, mixed for 7.5 minutes at a temperature of 135° C., and then discharged, cooled and pelletized to obtain a colored ultra-thin coating modifier; Example 6 The only difference from Example 2 is step S4: 95 parts of inorganic pigment, 135 parts of modified styrene-butadiene-styrene block copolymer, 3 parts of carbon nanotubes and 15 parts of plasticizer are weighed by weight, and added into a double-roll mill, mixed for 7.5 minutes at a temperature of 135° C., and then discharged, cooled and pelletized to obtain a colored ultra-thin coating modifier; Example 7 The only difference from Example 2 is step S4: 95 parts of inorganic pigment, 135 parts of styrene-butadiene-styrene block copolymer, 3 parts of carbon nanotubes and 15 parts of plasticizer are weighed by weight, and added into a double-roll mill, mixed for 7.5 minutes at a temperature of 135° C., discharged, cooled and pelletized to obtain a colored ultra-thin coating modifier; Example 8 The difference from Example 2 is only in step S5: 62.5 parts of coarse aggregate, 35 parts of fine aggregate, 7.5 parts of limestone powder and 5.25 parts of asphalt are weighed by weight, the coarse aggregate and the fine aggregate are stirred and heated to 160° C., then asphalt and limestone powder are added, and stirring is continued for 45 seconds to obtain a colored mixture; For the above-mentioned Examples 1 to 8, experiments were conducted in accordance with the asphalt test standards of the "Testing Procedures for Asphalt and Asphalt Mixtures for Highway Engineering" (JTG E20-2011): needle penetration TO604-2011; immersion Marshall test T0709-2000; freeze-thaw splitting test T0729-2000; the experimental results are shown in Table 1 below; Table 1 From the comparison of the experimental data of Examples 1 to 3 in Table 1, it can be found that the color mixture prepared by the present invention has good low temperature resistance; The performance of Examples 4 to 7 gradually decreased. In Example 4, due to the lack of pyridine, SBS was not modified in Example 5, carbon nanotubes were not modified in Example 6, and both SBS and carbon nanotubes were modified in Example 7. From the data, it can be seen that the performance of the color mixture gradually decreased, and the decrease was most obvious in Example 8, because no color ultra-thin coating modifier was added therein; For the above-mentioned embodiments 1 to 8, splitting tensile strength tests were conducted. The tests were divided into three categories according to the asphalt test standard of "Testing Procedures for Asphalt and Asphalt Mixtures in Highway Engineering" (JTG E20-2011): Asphalt Mixture Splitting Test T0716-2011. The first category tested the splitting tensile strength of the initial sample, the second category tested ultraviolet aging, using a 1000W high-pressure mercury lamp to simulate ultraviolet irradiation for 100 hours, and then conducting a splitting tensile strength test, and the third category tested the low-temperature self-repairing performance test, using a blade to cut a section in the middle of the specimen, allowing the damaged sample to self-repair for 1 hour at 0°C, and then conducting a splitting tensile strength test; wherein, anti-aging performance = splitting tensile strength after ultraviolet aging / initial splitting tensile strength; low-temperature self-repairing performance = splitting tensile strength after low-temperature self-repair / initial splitting tensile strength; the test results are shown in Table 2 below; Table 2 From the comparison of the experimental data of Examples 1 to 3 in Table 2, it can be found that the color mixture prepared by the present invention has good anti-aging performance and low-temperature self-repairing performance; The anti-aging performance in Examples 5 and 7 decreases rapidly, mainly because the unmodified SBS has a large number of double bonds, which leads to a decrease in its anti-aging performance; and the low-temperature self-repairing ability except Example 5 decreases rapidly, mainly due to the lack of reversible metal coordination bonds.

[0020] It will be apparent to those skilled in the art that the invention is not limited to the details of the exemplary embodiments described above and that the invention can be implemented in other specific forms without departing from the spirit or essential features of the invention. Therefore, the embodiments should be considered in all respects as exemplary and non-limiting, and the scope of the invention is defined by the appended claims rather than the foregoing description, and it is intended that all variations within the meaning and scope of the equivalent elements of the claims be included in the invention. Any marking in a claim should not be considered as limiting the claim to which it relates.

Claims

1. A color mixture for preventive maintenance of asphalt pavement, characterized in that: The weight proportions of the components of the color mixture are: 55-70 parts of coarse aggregate, 20-50 parts of fine aggregate, 5-10 parts of limestone powder, 4.5-6 parts of asphalt and 2-6 parts of color ultra-thin coating modifier; The coarse aggregate has a specification of 3-5 mm, and the fine aggregate has a specification of 0-3 mm; the asphalt is 70# or 90# heavy-duty road petroleum asphalt.

2. The color mixture for preventive maintenance of asphalt pavement according to claim 1, characterized in that: The weight proportions of the components in the colorful ultra-thin coating modifier are: 90-100 parts of inorganic pigment, 120-150 parts of modified styrene-butadiene-styrene block copolymer, 1-5 parts of modified carbon nanotubes and 0-30 parts of plasticizer.

3. The color mixture for preventive maintenance of asphalt pavement according to claim 2, characterized in that: The modified styrene-butadiene-styrene block copolymer adopts 3-mercaptopropionic acid through a mercapto-ene click chemical reaction, so that 3-mercaptopropionic acid reacts with double bonds in the styrene-butadiene-styrene block copolymer to modify the styrene-butadiene-styrene block copolymer, thereby obtaining the modified styrene-butadiene-styrene block copolymer.

4. The color mixture for preventive maintenance of asphalt pavement according to claim 2, characterized in that: The modified carbon nanotubes are prepared by chain extension reaction of diamine-terminated polydimethylsiloxane and 2,6-pyridine dicarbonyl chloride, and then grafting reaction is carried out between the modified diamine-terminated polydimethylsiloxane and acyl chloride carbon nanotubes to obtain the modified carbon nanotubes.

5. A method for preparing a colored mixture for preventive maintenance of asphalt pavement, characterized in that: The method comprises the following preparation steps: S1. Weigh the inorganic pigment, modified styrene-butadiene-styrene block copolymer, modified carbon nanotube and plasticizer according to the above weight proportions, add them into a double-roll mill, mix them for 5-10 minutes at a temperature of 130-140° C., discharge them, cool them and pelletize them to obtain a colored ultra-thin coating modifier; S2. Weigh the coarse aggregate, fine aggregate, limestone powder, asphalt and colored ultra-thin surface modifier according to the above-mentioned weight proportions, stir and heat the coarse aggregate and fine aggregate to 150-170°C, then add the colored ultra-thin surface modifier and stir for 5-15s, then add the asphalt and limestone powder, and continue stirring for 30-60s to obtain a colored mixture.

6. The method for preparing a colored mixture for preventive maintenance of asphalt pavement according to claim 5, characterized in that: The modified styrene-butadiene-styrene block copolymer comprises the following preparation steps: adding the styrene-butadiene-styrene block copolymer to cyclohexane with a mass of 20 to 22 times that of the styrene-butadiene-styrene block copolymer, stirring evenly, adding azobisisobutyronitrile with a mass of 0.5% to 0.75% of that of the styrene-butadiene-styrene block copolymer, dripping 3-mercaptopropionic acid with a mass of 0.7 to 0.9 times that of the styrene-butadiene-styrene block copolymer at a temperature of 0 to 5° C. and under nitrogen protection, reacting for 10 to 15 minutes after the dripping is completed, heating to 55 to 65° C. and reacting for 12 to 14 hours, adding anhydrous ethanol with a mass of 2 to 3 times that of the cyclohexane after the reaction is completed, stirring, filtering, washing the filtered product with anhydrous ethanol and deionized water for 3 to 5 times respectively, and drying to obtain the modified styrene-butadiene-styrene block copolymer.

7. The method for preparing a colored mixture for preventive maintenance of asphalt pavement according to claim 5, characterized in that: The modified carbon nanotube The method comprises the following steps: adding chlorinated carbon nanotubes to N,N-dimethylformamide with a mass of 15 to 20 times that of the chlorinated carbon nanotubes, ultrasonically dispersing for 15 to 20 minutes, uniformly dropping a modified diamine-terminated polydimethylsiloxane solution with a mass of 5 to 7 times that of the chlorinated carbon nanotubes at a speed of 2 to 3 mL / min under the condition of a temperature of 0 to 5°C, stirring for 24 to 28 hours under the condition of a temperature of 25 to 35°C after the dropping is completed, standing and filtering after the stirring is completed, and drying and grinding the filtered product to obtain the modified carbon nanotubes.

8. The method for preparing a colored mixture for preventive maintenance of asphalt pavement according to claim 7, characterized in that: The modified diamine-terminated polydimethylsiloxane solution comprises the following preparation steps: adding the modified diamine-terminated polydimethylsiloxane to N,N-dimethylformamide with a mass 12 to 14 times that of the modified diamine-terminated polydimethylsiloxane, stirring evenly, preparing a modified diamine-terminated polydimethylsiloxane solution for standby use.

9. The method for preparing a colored mixture for preventive maintenance of asphalt pavement according to claim 8, characterized in that: The modified diamino-terminated polydimethylsiloxane comprises the following preparation steps: under nitrogen protection, adding diamino-terminated polydimethylsiloxane to dichloromethane with a mass of 10 to 12 times that of the diamino-terminated polydimethylsiloxane, stirring and dissolving, adding triethylamine with a mass of 0.03 to 0.05 times that of the diamino-terminated polydimethylsiloxane at a temperature of 0 to 5° C., stirring and reacting for 2 to 2.5 hours, adding 2,6-pyridinedicarbonyl chloride solution with a mass of 0.3 to 0.5 times that of the diamino-terminated polydimethylsiloxane at a uniform speed of 5 to 8 mL / min after the stirring is completed, stirring and reacting for 2 to 2.5 hours at a temperature of 0 to 5° C., stirring and reacting for 24 to 26 hours at a temperature of 25 to 35° C. after the reaction is completed, removing the dichloromethane solvent by rotary evaporation, and vacuum drying after the rotary evaporation to obtain the modified diamino-terminated polydimethylsiloxane.

10. The method for preparing a colored mixture for preventive maintenance of asphalt pavement according to claim 9, characterized in that: The 2,6-pyridinedicarbonyl chloride solution comprises the following preparation process: adding 2,6-pyridinedicarbonyl gas to dichloromethane with a mass of 10 to 12 times that of 2,6-pyridinedicarbonyl gas, stirring evenly, and preparing a 2,6-pyridinedicarbonyl chloride solution for standby use.

Citation Information

Patent Citations

  • Method for modifying styrene-butadiene-styrene (SBS) block copolymer

    CN102391424A

  • Colored permeable pavement asphalt mixture, preparation and application thereof

    CN108483999A

  • Colored asphalt mixture with excellent performance and preparation method thereof

    CN108610600A

  • Ultrathin overlay mixture for preventive maintenance of asphalt pavement, preparation method and additive

    CN114075053A

  • Pavement structure adopting warm mixing ultrathin layer overlay and construction method of pavement structure

    CN114351529A